Chemical stability of naloxone products beyond their labeled expiration dates - Hossain, PhD, Mohammad F.; Rashid, PhD, Mamoon; Mullins, PharmD, Randy; Davis, PharmD, Tiffany; Kimble, PharmD, MBA, MS, BCACP, Craig; Sarkar, MS, PharmD, Sushanta; Babcock, PharmD, CDE, BCACP, Charles “CK” (Journal of Opioid Management, 2022)
Objective: The purpose of this study was to evaluate the chemical stability of previously dispensed, expired naloxone products. Setting: When properly stored, certain products maintain stable, defined as within compendia acceptability, beyond their manufacturer’s expiration date. Stockpiling life-saving medications such as the opioid overdose reversing agent naloxone nasal spray (NNS) or injection (NIJ) is of utmost importance to ensure public health emergency preparedness and response. Design/interventions/methods: After each naloxone product was stored at room temperature for several months (6-19) past their labeled expiration date, the level of active therapeutic content and the presence of degradation impurity, 2,29-bisnaloxone, were evaluated via chromatographic separation with waters higher performance liquid chromatography integrated using the Waters X-Select CSHC-18. The effluent was detected at 229 nm. Main outcome measure: Active naloxone presence and the presence of degradation impurity, 2,29-bisnaloxone, were evaluated. Results: The mean potency of naloxone in both NNS and NIJ, up to 10 and 19 months post-expiration, respectively, is within the 90-110 percent United States Pharmacopeia acceptance limit (NNS: 102.8 ± 2.6 percent and NIJ: 106.0 ± 1.3 percent). No impurity was detected in any chromatogram of the expired products. Conclusion: In summary, since both NNS and NIJ were found to be chemically stable beyond 10 months of the expiration date, shelf-life extension of climate controlled, commercially available naloxone products should be further investigated as a potential cost savings measure for national strategic stockpiles, emergency medical services, hospitals, and public responders.